Metabolic Rewiring of Mycobacterium tuberculosis upon Drug Treatment and Antibiotics Resistance - Biplab Singha; Sumit Murmu; Tripti Nair; Rahul Singh Rawat; Aditya Kumar Sharma; Vijay Soni (Metabolites, 2024)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a significant global health challenge, further compounded by the issue of antimicrobial resistance (AMR). AMR is a result of several system-level molecular rearrangements enabling bacteria to evolve with better survival capacities: metabolic rewiring is one of them. In this review, we present a detailed analysis of the metabolic rewiring of Mtb in response to anti-TB drugs and elucidate the dynamic mechanisms of bacterial metabolism contributing to drug efficacy and resistance. We have discussed the current state of AMR, its role in the prevalence of the disease, and the limitations of current anti-TB drug regimens. Further, the concept of metabolic rewiring is defined, underscoring its relevance in understanding drug resistance and the biotransformation of drugs by Mtb. The review proceeds to discuss the metabolic adaptations of Mtb to drug treatment, and the pleiotropic effects of anti-TB drugs on Mtb metabolism. Next, the association between metabolic changes and antimycobacterial resistance, including intrinsic and acquired drug resistance, is discussed. The review concludes by summarizing the challenges of anti-TB treatment from a metabolic viewpoint, justifying the need for this discussion in the context of novel drug discovery, repositioning, and repurposing to control AMR in TB.